HUMAN RESOURCE AND SUPPLY CHAIN STRATEGY TO IMPROVE COMPANY PERFORMANCE THROUGH ORGANIZATIONAL CAPABILITY IN PT POS INDONESIA - Febrisi Dwita; Stefanus M. Sri Sadana (Universitas Airlangga, 2021)
Growing services companies caused a tighten business competition in market for shipping goods and document packages. Providing best service strategy and also presenting a variety of innovative services for delivering goods and document attract many consumers. The research has a goal to test whether there is an influence between strategic human resource management (SHRM), strategic supply chain management (SCM) through company capabilities on improving performance of Indonesian Postal Companies in Bekasi area. The research was conducted at Head Office of PT Pos Indonesia Bekasi City. Questionnaires of each variables distributed in form of questions that represent dimensions with a total sample of 156 respondents. To analyze data used SEM with help of AMOS software. Finally, following research results were obtained: (1) implementation of SHRM has a positive and significant effect on organizational capability; (2) implementation of SCM strategies has a positive and significant effect on organization capability; (3) implementation of SHRM has a positive and significant effect on SCM strategy; (4) organizational capability has a positive and significant effect on company performance; (5) implementation of SCM strategy has a positive and significant effect on performance through organizational capabilities and (6) level of implementation of SHRM has a positive and significant effect on company performance through organizational capabilities. From results of study, it is suggested that organizations focus more on developing organizational capabilities, especially through strategic HRM as business partner and SCM strategy.